PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN MELALUI FAKTOR RISIKO TEKANAN DAN PELUANG (Studi Kasus pada Perusahaan yang Mendapat Sanksi dari Bapepam Periode 2002-2006) - Martantya Maudy Rahmanti; daljono daljono (Diponegoro Journal of Accounting, 2013)
This study aims to obtain empirical evidence about the effectiveness of the fraud triangle ispressure, opportunity, and rationalization in detecting financial statements fraud. Based on thetheory of fraud triangle Cressey adopted in SAS 99, the researchers developed a variable that canbe used to proxy the size of the components of the pressure and opportunity. The variables of thefraud triangle used is pressure consisting of financial stability are proxied by asset growth(AGROW), external pressure are proxied by leverage (LEV), managerial ownership are proxied bythe presence or absence of share ownership by insiders (OSHIP), and financial targets are proxiedby the return on assets (ROA), and opportunity consisting of effective monitoring proxied by theproportion of independent commissioners (IND). Data on indications of financial statements fraudin this study obtained from the annual report and press releases Bapepam during 2002 - 2006 asthe dependent variable. Total sample was 62 companies, consisting of 31 companies who violatedBapepam contain elements of fraud as well as sanctions, and 31 companies that are not financialstatements fraud (based on the type of industry and the total assets of the same). Testing thehypothesis used the logistic regression method. The results of this study indicated that financialstability are proxied by asset growth and financial targets proxied by ROA significantly related tothe possibility of financial statements fraud. While external pressure, managerial ownership, andineffective monitoring did not significantly influence the likelihood of financial statements fraud,and the size of the company can not be used as control variables in this study.